A signal-off aptasensor for the determination of Ochratoxin A by differential pulse voltammetry at a modified Au electrode using methylene blue as an electrochemical probe. Issue 37 (7th September 2017) - Wei, Min; Feng, Shuo
Abstract : A signal-off aptasensor for OTA detection at an apt/cDNA/AuNPs/cPC/NH2 –AuE electrode using methylene blue as an electrochemical probe. Abstract : In this work, a novel signal-off aptasensor was constructed for the determination of Ochratoxin A (OTA) using differential pulse voltammetry. Methylene blue (MB) was used as an electrochemical indicator by intercalating into a single-stranded aptamer through guanine bases and double-stranded DNA and produced a strong current signal. The prepared carboxylic porous carbon (cPC) and Au nanoparticles (AuNPs) are successively utilized to modify an aminated Au electrode (AuNPs/cPC/NH2 –AuE), which not only enables a higher loading of the capture DNA (cDNA), but also effectively enhances the electron transfer between MB and the electrode surface to improve the determination sensitivity. By immobilization of cDNA and hybridization with the aptamer on the AuNPs/cPC/NH2 –AuE, the apt/cDNA/AuNPs/cPC/NH2 –AuE sensor was constructed. In the presence of OTA, the complex formation between the aptamer and OTA prohibited the binding between cDNA and the aptamer, which led to the release of MB from the electrode surface and a decreased amount of adsorbed MB, producing a lowered electrochemical signal. The change of the MB electrochemical signal can be applied for OTA detection. The linear relationship between the change of peak current and the logarithmic concentration of OTA was observed in the range of 5.0 × 10 −6 –5.0 × 10 −4 ng mL −1 with a correlation coefficient of 0.999. The experimental results showed that the prepared apt/cDNA/AuNPs/cPC/NH2 –AuE sensor had acceptable reproducibility, repeatability and specificity.